2007
DOI: 10.1002/pon.1216
|View full text |Cite
|
Sign up to set email alerts
|

The importance of expectations on the recovery period after cancer treatment

Abstract: The purpose was to study expectations concerning recovery-related changes in life, e.g. beliefs regarding future adjustment back to 'normal' life after curative cancer treatment, whether these expectations were met and their importance for both patients' and their spouses' quality of life and psychological distress. Sixty-two patients and 42 spouses took part in the study. Data on recovery-related expectations, measured using a study-specific questionnaire (RRE), on quality of life using EORTC-QLQ C-30 and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
4
21
1
Order By: Relevance
“…Nevertheless, they had to handle a situation with pain and nutrition problems, fatigue, and psychological distress i.e., experiences common in a less than optimized palliative situation, by themselves (World Health Organization, 2002). The relatively dark picture of the situation and of the future reported by the relatives in our study differs from at least one other study (Winterling et al, 2008) Several studies of cancer patients and their relatives have reported that the common experience of a difficult situation has resulted in positive changes in the relationship (Drabe et al, 2013;Ruf et al, 2009). This was also the case in our study in which several relatives noted that they had become closer to the patient.…”
Section: Discussioncontrasting
confidence: 97%
“…Nevertheless, they had to handle a situation with pain and nutrition problems, fatigue, and psychological distress i.e., experiences common in a less than optimized palliative situation, by themselves (World Health Organization, 2002). The relatively dark picture of the situation and of the future reported by the relatives in our study differs from at least one other study (Winterling et al, 2008) Several studies of cancer patients and their relatives have reported that the common experience of a difficult situation has resulted in positive changes in the relationship (Drabe et al, 2013;Ruf et al, 2009). This was also the case in our study in which several relatives noted that they had become closer to the patient.…”
Section: Discussioncontrasting
confidence: 97%
“…In a similar line of research (Winterling, Glimelius, & Nordin, 2008), a mixed cancer population reported recovery-related expectations before treatment; these expectations were correlated to patients' later quality of life. In general, patients had high expectations regarding their later physical and psychological health.…”
mentioning
confidence: 90%
“…Only one intervention study tested whether a cognitive behavioral intervention modified cognitive factors (perceived stress management skills), and whether improvement in QoL was mediated by greater perceived skills [11]. Other studies suggested cognitive factors such as: fear of recurrence [12, 13], belief in curability [14], recovery expectations [1517], cognitive appraisal of cancer threat [18], and patients' perceptions of their illness and treatment [1921]. …”
Section: Introductionmentioning
confidence: 99%